SHM_415720_HST_3D North Bothnian Stone Implement - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a North Bothnian stone implement (Swedish: Nordbottniskt redskap) from the Swedish Neolithic or Early Bronze Age, collected in the field from Karesuando Parish in Norrbotten and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=420

Link to Sök I Samlingarna

https://samlingar.shm.se/object/251FE160-4588-46F6-A24B-ED900EE8AED5
Keywords: Archaeology; Archaeology; Archaeology/history; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Swedish Neolithic; Swedish Bronze Age; Karesuando; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi